Conversion of biomass waste to solid fuel via hydrothermal co-carbonization of distillers grains and sewage sludge. (February 2022) - Zhao, Jiamin; Liu, Chang; Hou, Tingting; Lei, Zhongfang; Yuan, Tian; Shimizu, Kazuya; Zhang, Zhenya
Graphical abstract: Highlights: Fuel properties were improved by HTcoC of distillers grains and sewage sludge. The synergistic effect and mechanism involved in HTcoC were discussed. Combustion behaviors of hydrochar from HTcoC were improved. HTcoC enhanced the biofuel recovery rate and net energy gain. Abstract: A synergistic process was proposed to prepare hydrochar by hydrothermal co-carbonization (HTcoC) of waste distillers grains with sewage sludge, focusing on hydrochar properties and combustion behavior under different mixing ratios. Results show that the co-hydrochar from HTcoC exhibited excellent synergistic characteristics with relatively high synergistic coefficients (0.1–1.2% for hydrochar yield, 4.8–8.0% for higher heating value (HHV), 8.0–12.6% for organic retention, and 2.2–4.0% for carbon retention, respectively), partially evidenced by FTIR data. And the co-hydrochar showed a higher fuel ratio of 0.09–0.13 with the fixed carbon increased to 8.3–10.0 at an remarkably enhanced coalification degree. Moreover, thermal analysis showed that the co-hydrochar exhibited improved combustion efficiency and a more stable flame. As a result, the HTcoC process with 13.0–22.5% increase in biofuel recovery rate and 25.6–47.7% increase in net energy gain may provide an effective approach for the conversion of both biomass wastes into clean biofuel.